Pendekatan Konseling pada Anak Korban Keluarga Broken Home; Literature Review - Putri, Nurul Faiza Eka; Sihombing, Melani Lestari; Syahidah, Nabila Alifiana; M, Muslikah; Mahfud, Ashari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The loss of family unity creates deep emotional wounds that hinder the psychological growth of children. This study aims to examine the effectiveness of various counseling approaches in supporting the recovery of children from broken homes. This research employed a literature review method by analyzing scientific papers, articles, and relevant books. The findings show that community counseling, peer groups, sociodrama, and culturally-based counseling approaches strengthen resilience, enhance emotional well-being, and develop social skills in children. It is recommended that counselors, teachers, and communities collaborate to build a responsive and sustainable support ecosystem for children from broken families.